2013
DOI: 10.1302/0301-620x.95b5.30181
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of proximal and distal chevron osteotomy for the correction of moderate hallux valgus deformity

Abstract: The purpose of this study was to compare the results of proximal and distal chevron osteotomy in patients with moderate hallux valgus. We retrospectively reviewed 34 proximal chevron osteotomies without lateral release (PCO group) and 33 distal chevron osteotomies (DCO group) performed sequentially by a single surgeon. There were no differences between the groups with regard to age, length of follow-up, demographic or radiological parameters. The clinical results were assessed using the American Orthopaedic Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
2
27
1
1
Order By: Relevance
“…Recently, Park et al compared proximal and distal chevron osteotomies in 77 feet [69]. In contrast to the results of our study compared with the meta-analysis of Smith et al they found no statistically significant difference for correction of HVA and IMA.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Park et al compared proximal and distal chevron osteotomies in 77 feet [69]. In contrast to the results of our study compared with the meta-analysis of Smith et al they found no statistically significant difference for correction of HVA and IMA.…”
Section: Discussioncontrasting
confidence: 99%
“…Fokter et al (1) reported on the late results of the Mitchell osteotomy with a mean corrected IMA of 7.7 . The amount of shortening of the first metatarsal in the chevron osteotomy group was also comparable to that reported in current studies (4.2 mm) (24).…”
Section: Discussionsupporting
confidence: 89%
“…This soft tissue procedure aims to restore the physiological balance of capsular, ligamentous and muscular structures around the first metatarsophalangeal (MTP) joint. During the last decades worldwide scientific discussions, clinical surveys [1][2][3][4][5][6][7][8], anatomical studies [9,10] and experimental set-ups [11][12][13][14] have helped to clarify open questions about soft tissue procedures: is it necessary in every case of bunion surgery and is there a technique superior in respect of high efficiency and low risk? Certain reservations exist regarding the combination of distal soft tissue procedures and distal metatarsal osteotomies.…”
Section: Introductionmentioning
confidence: 99%